Four years into NextGenerationEU: What impact on the euro area economy? - Krzysztof Bańkowski; Nicholai Benalal; Othman Bouabdallah; Roberta De Stefani; Ettore Dorrucci; Christian Huber; Pascal Jacquinot; Wolfgang Modery; Carolin Nerlich; Marta Rodríguez Vives; Bela Szörfi; Nico Zorell; et al. (European Central Bank (ECB), 2024)
This paper takes stock of the implementation of the NextGenerationEU (NGEU) programme in the euro area four years after its inception, focusing on its principal instrument, the Recovery and Resilience Facility (RRF). The paper provides an updated quantitative assessment of its past and future impact on the euro area economy, using a set of models and scenarios to account for the uncertainty that still surrounds the implementation of this programme. The public expenditures and structural reforms linked to the RRF have the potential to increase the level of euro area gross domestic product (GDP) by around 0.4-0.9% by 2026 and 0.8-1.2% by 2031, depending on capital productivity and the degree of absorption of RRF funds. The contribution of structural reforms to these output effects is expected to increase over time, while the initially prevailing impact of RRF-funded public expenditures fades away. We provide tentative empirical evidence that reforms have started to modestly improve the growth outlook of some euro area Member States by increasing their institutional quality. The expected long-run increase in output is in turn a key factor behind the decline in the government debt ratios we project for the main NGEU beneficiary euro area Member States. At the same time, we estimate that NGEU will have a limited impact on euro area inflation. Compared with previous ECB staff analysis published in 2022, the macroeconomic impact of NGEU, particularly on GDP and government debt ratios, is expected to shift over time due to widespread delays in the implementation of NGEU-linked expenditures and reforms. It is crucial that euro area Member States address implementation challenges over the remaining lifetime of this programme to fully reap its benefits.
Keywords: C54; E02; E22; E62; F45; H87; O52; 330; NGEU; RRF; structural reforms; public investment; economic consequence; economic recovery; community resilience; foresight; euro area; structural adjustment